Satisfaction with general practice care in German patients with multimorbidity: a cross-sectional study. (21st February 2017) - Mortsiefer, Achim; Altiner, Attila; Ernst, Annette; Kadusziewicz, Hanna; Krahe, Alice; Mellert, Christine; Schäfer, Ingmar; Stolzenbach, Carl-Otto; Wiese, Birgitt; Löffler, Christin
Abstract: Background: Little is known about the quality of general practice care received by patients suffering from multimorbidity. Objectives: To assess how patients with multimorbidity evaluate their General Practitioners (GPs') performance and to identify factors associated with high patient satisfaction levels. Methods: Cross-sectional study in Germany using the EUROPEP questionnaire consisting of 23 items with a five-point Likert scale and covering two dimensions: clinical performance of the GP and organisation of care. Mixed logistic regression was used in the analysis, with the EUROPEP score as a dependent variable. Results: The study included 651 patients (54.8% female), with a mean age of 73.7 ± 4.9 years. Of 22 of 23 questionnaire items, >80% of patients rated their satisfaction as 'good' or 'excellent'. The highest level of satisfaction (excellent) varied among items between 28.0 and 73.1%. Lower age and female sex of GPs were associated with better patient evaluations in 15 and 12 of the 23 items, respectively. Patient characteristics were not associated with their satisfaction with their GP. Conclusions: This study found high levels of satisfaction with primary care in patients with multimorbidity. However, since high levels of patient satisfaction are not necessarily equivalent to high quality of care, a broader view is necessary to integrate the subjective views of patients and objective quality indicators into a comprehensive concept of good quality of care.